Design of Distance English Teaching Application System Combined with Behavioral Cognitive Settlement - Wenqin Liu (Advances in Multimedia)
In order to improve the quality of Distance English teaching, this study studies the teaching application system combined with behavioral cognition. In the research, relevant technologies such as settlement system integration, automatic scoring, data encryption, authority control and problem matching are introduced, and the system is improved. This process promotes the social and economic benefits brought by this kind of system with the help of various verification methods. At the same time, it also summarizes the advantages of Distance English teaching, and finally realizes the effective analysis of this kind of system. The design of the Distance English teaching application system is of great help to the follow-up teaching work. Therefore, we need to actively design such a system to optimize the quality of English teaching and lay a good foundation for teachers’ follow-up teaching.